'We always had things to do': The Paid and Unpaid Work of Anglophone Children Between the 1920s and the 1960s - Sutherland, Neil (Labour/Le Travailleur, 1990)
Abstract By the 1920S child labour and school attendance legislation had almost eliminated the full-time labour of those under fifteen. However, interview data show that both middle- and working-class Canadian children continued to do a great deal of work in their households. Many young boys and girls also worked at regular and irregular part-time paying jobs. The earnings of working-class children often stood between their families and real economic hardship, while those of middle-class youngsters reduced pressure on tight family budgets. In addition to its contribution to family economies, children's work played a considerable role in developing the gender identities of both girls and boys.